Deconstructionist and poststructuralist translation approaches: overview and critique (2008)
It has become a commonplace to believe that deconstructionist and poststructuralist views on translation have opened new perspectives in Translation Studies. In this paper, I attempt to show what the main tenets by the main authors in these theories are (Benjamin, Derrida, Berman, Venuti). I also try to show the line of thought that goes from Benjamin to Berman and Derrida and then to Venuti. Likewise, I focus my attention especially on a well-known controversy between Derrida and Searle on key aspects of language meaning. In the second part of the paper, I present the main criticisms made by Newmark, Pym, Searle, Arrojo, and Tymoczko, among others, to the deconstructionist and poststructuralist translation views of interpretation. Finally, I draw some conclusions.